Fugitive methane emissions from two agricultural biogas plants. (September 2022) - Baldé, Hambaliou; Wagner-Riddle, Claudia; MacDonald, Douglas; VanderZaag, Andrew
Graphical abstract: Highlights: Inverse dispersion was used to measure CH4 -losses from two biogas plants over 1 y. Digestate storage was the largest contributor at both facilities. Digestate emissions were lower with longer digester HRT and solids removal. Leakage/venting emissions were intermittent, and were low after maintenance. Flaring emissions were the smallest contributor (<0.25 %) Abstract: This study quantified fugitive methane (CH4 ) losses from multiple sources (open digestate storages, digesters and flare) at two biogas facilities over one year, providing a much needed dataset integrating all major loss pathways and changes over time. Losses of CH4 from Facility A were primarily from digestate storage (5.8% of biogas CH4 ), followed by leakage/venting (5.5%) and flaring (0.2%). At Facility B, losses from digestate storage were higher (10.7%) due to shorter hydraulic retention time and lack of a screwpress. Fugitive emissions from leakage were initially 3.8% but were reduced to 0.6% after the dome membrane was repaired at Facility B. For biogas to have a positive impact on greenhouse gas emissions and provide a low-carbon fuel, it is important to minimize fugitive losses from digestate storage and avoid leakage during abnormal operation (leakage, roof failure).